Systematic and taxonomic observations on the subfamily Synapseudinae Guţu, 1972 and related metapseudid taxa (Crustacea: Tanaidacea: Apseudomorpha), with the erection of a new genus and descriptions of three new species - Heard, Richard W.; Stępień, Anna; Drumm, David T.; Błażewicz, Magdalena; Anderson, Gary (Zootaxa, 2018)
The tanaidacean metapseudid subfamily Synapseudinae Guţu is reviewed, partially revised and the type species, Synapseudes minutus Miller, redescribed. As rediagnosed and defined here, the Synapseudinae is restricted to the genera Synapseudes Miller, Vicinisyndes Guţu, and Creefs Stępień & Błażewicz-Paszkowycz. The genera Curtipleon Băcescu and Cryptapseudes Băcescu are excluded from this subfamily. Three new species, S. caleyi, S. singularis, and S. hansknechti are described, bringing the number of putative species within the genus to 26. An identification key and table of selected specific characters for the species of Synapseudes are provided. A new monotypic genus, Ronabus, which is placed within the subfamily Metapseudinae Lang, is erected to receive Synapseudes idios Gardiner. The present taxonomic status of subfamilies within the Metapseudidae is briefly assessed.